PKM Pelatihan Aplikasi Zahir Accounting Laporan Keuangan - Nining Rahaningsih; Gifthera Dwilestari; Rudi Kurniawan; Ahmad Rizki Fauzi; Fazri Muzaki (CV. Multi Kreasi Media, 2023)
Accurate and timely financial reporting is key to the success of business operations, especially for Small and Medium Enterprises (SMEs). However, many SMEs still face difficulties in preparing financial reports that comply with applicable accounting standards. Limited understanding of accounting and the use of technology are the main barriers. To address this issue, this program aims to provide training on the use of Zahir Accounting software as a solution for preparing financial reports. The methods used include intensive training, case studies, and direct simulations of using the Zahir Accounting application. The results of this program are expected to enhance participants' abilities to prepare accurate and standardized financial reports, thereby supporting better decision-making in their businesses. Additionally, this program is expected to improve the efficiency and effectiveness of financial management within SMEs.